Exploring Modernity, Nurturing Tradition: The Pesantren Leaders' Journey in Japan - Fadlan, Muhammad Nida' (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
The COVID-19 pandemic, from early 2020, compelled rigorous border restrictions among nations. Travel between countries became virtually impossible to curb the virus's rampant spread. All plans involving face-to-face human interactions had to be abandoned except for essential pandemic-related activities. Consequently, the scheduled leaders' visits from Indonesian Islamic boarding schools (pesantren) to Japan during this period had to be withdrawn as well.This annual event, initiated in 2004 through collaboration between the Center for the Study of Islam and Society (PPIM) at Syarif Hidayatullah State Islamic University of Jakarta and the Government of Japan, aims primarily to enhance understanding and cultivate friendship between Japan and Indonesia, particularly among the Muslim community. Over nearly two decades, this program facilitated the participation of 157 leaders (kiai and nyai) from diverse regions in Indonesia, enabling them to observe contemporary developments in Japanese society while exchanging insights into the characteristics of Indonesia's Muslim community with the local people. Domestically, this initiative also desired to strengthen networks among pesantrens.